Crecimiento Poblacional y Productividad de la Microalga Nativa Chlorella peruviana bajo Diferentes Salinidades - Mariano Astacondor, Mauro (2017)
The aim of the study was to evaluate five salinity levels on the growth and productivity of Chlorella peruviana Chacon, a native strain of the Mellisera salt lagoon in Chilca, Peru. Five treatments were used according to the salinity level: T1, 38‰; T2, 44‰; T3, 59‰; T4, 88‰; and T5, 176‰, with a temperature of 27±2 °C and a light intensity of 1250±10 lx. Each treatment was done in triplicate in flasks of 250, 500 and 1000 ml. Cultures were performed with f/2 medium (Guillard), constant aeration and photoperiod of 24:00 h. The results indicated that T1 showed better results in density (42±2.65x106 cel/ml), dry biomass (397.9±2.3 mg/l) and chlorophyll (80.2±2.3 mg/l), but with adequate yields at higher levels of salinity. It is concluded that the growth and productivity of C. peruviana presents a decreasing trend in relation to the level of salinity.